STUDI BIOGRAFI TOKOH DAHLAN ISKAN DALAM SEJARAH INDONESIA - Deska Mardila Fitri Mui (Al-Fikru : Jurnal Pendidikan Dan Sains, 2022)
Dahlan Iskan is a national figure who has contributed to advancing the Indonesian state. Dahlan Iskan is known to the wider community as a former CEO of the Javanese newspaper Pos Grub, President Director of PLN and has also been one of the State Ministers of State-Owned Enterprises (BUMN). He is someone who should be emulated and exemplified by everyone, especially for the younger generation, especially in his character from his life journey in fighting for the advancement of the Indonesian state. The author uses the method in making this article is the library research method and historical research methods. The library research method is a series of activities related to the library data collection method (Mahmud, 2011: 31). In addition, the author also uses the historical research method which includes several series of steps in the form of the Heuristic method, source criticism, analysis and interpretation, and historiography. This article contains a biographical history of an Indonesian figure named Dahlan Iskan with the formulation of problems regarding the life history of Dahlan Iskan, how the history of the progress of BUMN and Indonesian newspapers by Dahlan Iskan, and how the character of discipline, hard work, and never giving up is owned by Dahlan Iskan. . The research of making this article aims to describe or analyze and get an overview of the character values ​​possessed by the character Dahlan Iskan in a novel written by Sholihin Hidayat. Keywords: Dahlan Iskan, Discipline, Never Give Up, BUMN, Newspaper .